Redesign of the Chlamydomonas reinhardtii QB binding niche reveals photosynthesis works in the absence of a driving force for QA‐QB electron transfer - Lambreva, Maya D.; Zobnina, Veranika; Antal, Taras K.; Peeva, Violeta N.; Giardi, Maria Teresa; Bertalan, Ivo; Johanningmeier, Udo; Virtanen, Olli; Ray, Mithila; Mulo, Paula; Polticelli, Fabio; Tyystjärvi, Esa; et al. (Wiley, 2025)
An in silico redesign of the secondary quinone electron acceptor (QB) binding pocket of the D1 protein of Photosystem II (PSII) suggested that mutations of the F265 residue would affect atrazine binding. Chlamydomonas reinhardtii mutants F265T and F265S were produced to obtain atrazine-hypersensitive strains for biosensor applications, and the mutants were indeed found to be more atrazine-sensitive than the reference strain IL. Fluorescence and thermoluminescence data agree with a weak driving force and confirm slow electron transfer but cannot exclude an additional effect on protonation of the secondary quinone. Both mutants grow autotrophically, indicating that PSII requires strong light for optimal function, as was the case in the ancestral homodimeric reaction center.